REVITALISASI DAN EKSPLORASI KEARIFAN LOKAL (LOCAL WISDOM) DALAM KONTEKS PEMBANGUNAN KARAKTER BANGSA - Santosa, Edi (FORUM, 2012)
traditional culture, including local knowledge, a sign of backwardness and obstacles inachieving socio-economic progress. An opinion that further strengthen the polarization betweenindigenous innovation. Local culture (also often called cultural areas) is the term commonly used todistinguish a culture of national culture (Indonesia) and global culture. Local culture is a culture that isowned by the people who occupy a particular locality or region different from the culture of which isowned by the people who are in a different place